Javanese cultural content and identity construction: study on javanese transmigrant descendants In Lampung, Indonesia - Dhanik Sulistyarini; Wahyudi Kumorotomo Rajiyem (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article discusses the role of media, especially Javanese cultural content, in the construction of the cultural identity of the Javanese transmigrant descendants in Lampung, Indonesia. The formulation of the problem in this study is how the role of Javanese cultural content in the construction of the identity of the descendants of Javanese transmigrants--in particular third and fifth generation--in Lampung? It is further divided into three research questions, which are how is Javanese cultural content displayed in the media in Lampung? What media are consumed by the descendants of Javanese transmigrants in Lampung? How does Javanese cultural content in the media play a role in the construction of the cultural identity of Javanese transmigrants in Lampung? This is a case study research, and the data was collected through in-depth interviews with 8 descendants of Javanese transmigrants in Lampung, 3 local media managers, and participative observations. The results showed that the descendants of Javanese transmigrants used both traditional and digital media. Elderly informants used print media (Javanese-language magazine), radio, and television, as well as a small amount of digital media. Meanwhile, adolescent informants consume Javanese cultural content through digital media, especially YouTube and TikTok. These results prompted researchers to argue that media and technology play a role in the construction of transmigrants' identities. The Javanese cultural content helps transmigrants to maintain their Javanese cultural identity.